#TITLE_ALTERNATIVE# - NUR AYUDYA (NIM : 20515045), LAILATUL
Maltose is a fermentable sugar used in industrial processes such as brewing or baking. Mal11p is the maltose permease from budding yeast Saccharomyces cerevisiae and plays a role in maltose fermentation by transporting maltose (coupled to a proton) across the plasma membrane and into the cell. In this research, structure-based engineering of aromatic and polar residues in the central cavity of Mal11p was performed to find determinants of sugar binding. Mutations were constructed by site directed mutagenesis, using pRHA00L as the original template. The mutant plasmids were constructed by fragment ligation via homologous recombination in yeast S. cerevisiae IMK289. By screening mutants for correct cellular localization by fluorescence microscopy, it was found out one mutant was mislocalized. Maltose transport activity was assayed in vivo using 14C-maltose as a tracer, 0.1 M potassium citrate buffer at 30 ˚C. All mutants had reduced transport activity compared to the wild-type. W252Y, W252F, N249S, Q256S, Q256N, Q379S, Q379N, and Y507F were created to investigate further role(s) of putative binding-site residues maltose transport. Those mutants exhibited a significant decrease in transport activities, even though the substitute has similar side chain as the initial residue. Like the wild-type transporter, the transport activity of all mutants displayed a pH dependence that is indicative of proton-coupled maltose transport. The kinetic study data showed that most mutations lowered the affinity for maltose. The wild-type transporter had a Km of 4.5 mM and Vmax of 1.0 nmol (106 cells min)-1. Q225A and Y484A had similar Vmax and 5-fold increase in Km relative to the wild-type, W252Y had low Vmax and 10-fold increase in Km relative to the wild-type, Q379S and N380A had low Vmax and similar Km to the wild-type. In contrast, N249A, Q256A, and Q379A mutants showed a very high Km. Taken together, these results suggest that W252, N249, Q256, and Q379 are involved in critical interactions of sugar binding.